Analysis on spatial heterogeneity of ecological restoration demand in resource-based cities: taking Jiawang District of Xuzhou city as an example - Meinan CHEN; Zhongyi DING; Huping HOU; Qinglin NI; Xueqing WANG (Meitan kexue jishu, 2022)
After a long period of coal resource exploitation in resource-based cities, the imbalance and disharmony between resource development and ecological protection in coal mining areas are prominent. In the context of ecological civilization construction, clarifying the spatial heterogeneity of ecological restoration needs and reasonably arranging the priority of ecological restoration work will become the basic work for efficient and coordinated ecological protection and restoration, which will help to plan as a whole, coordinate and orderly promote the high-quality sustainable development of resource-based cities. From the comprehensive perspective of the coordinated development of ecosystem and human well-being, Jiawang District, Xuzhou City, was selected as an example, and the historical remote sensing images, historical mine information and social and economic statistics in 2000, 2010 and 2019 were taken as the data sources. The equivalent assignment method was used to calculate the regional ecosystem service value and make coefficient correction. The landscape ecological risk assessment system was constructed by integrating the topographic location index, mining area disturbance index and landscape vulnerability index. The spatial and temporal patterns of ecosystem service value and ecological risk index in the study area were analyzed, and the sharpe ratio was introduced to further explore the spatial heterogeneity of ecological restoration needs. The results showed that: ① From 2000 to 2019, the total value of ecosystem services in Jiawang district increased first and then decreased, and the value of ecological risk index decreased first and then increased. The growth rate was relatively flat, showing a small range; the spatial distribution of ecological service value and ecological risk level shows a trend of overall connectivity, with local circles moving outward. Urbanization and coal mining subsidence land management are the main factors influencing the spatial pattern differentiation. ② At the quantitative level, the ecosystem service value per unit area and the ecological risk index have strong negative grade correlations, but there is no obvious functional relationship; At the spatial level, the overall Moran’s I index of unit ecosystem service value and ecological risk index in Jiawang District from 2000 to 2019 were negative, showing negative spatial correlation. Ecological risks and ecosystem services have obvious dislocation characteristics. ③ The heterogeneity index R of ecological restoration demand in Jiawang district presents a gradient spatial change trend to a certain extent, and the overall ecological restoration demand tends to decrease, but the R index is still too high or too low in some regions; with the increase of degree of deviation, the range of high value areas for ecological restoration needs gradually narrowed and transformed to low value areas, and the areas requiring key ecological construction tend to be more centralized. The research conclusion can provide reference for the decision-making arrangement of systematic and integrated ecological restoration of resource exhausted cities.